Fashion : the definitive history of costume and style - Brown, Susan, 1965-; DK Publishing, Inc.; Smithsonian Institution (New York, N.Y. : DK Publishing, 2012)
"From simple to sophisticated, elegant to excessive, what we wear says who we are. "Fashion" is the ultimate visual guide to everything ever worn. From the extravagance of Ancient Egypt, through the legendary fashion houses of Chanel and Dior, to the latest cutting-edge labels, this gorgeous collection of costume and dress shows how fashion reflects people and places, and captures the times in which they lived"--Page 4 of cover.
Prehistory-600CE: the Ancient world -- 600-1449: Medieval romance and trade -- 1450-1624: Renaissance splendor -- 1625-1789: Baroque and Rococo -- 1790-1900: from revolution to frivolity -- 1901-1928: la belle epoque and the jazz age -- 1929-1946: from glamour to utility -- 1947-1963: optimism and youth -- 1964-1979: swinging sixties to glam rock -- 1980 onward: the designer decades.
Statement of responsibility from foreword.
Includes index.
Keywords: Fashion -- History; Clothing and dress -- History